Effects of corrosion on the strength of self-drilling screw connections in cold-formed steel structures-experiments and finite element modeling. (February 2022) - Roy, Krishanu; Ho Lau, Hieng; Fang, Zhiyuan; Masood, Rehan; Chui Huon Ting, Tina; Lim, James B.P.; Chieng Chen Lee, Vincent
Abstract: Cold-formed steel (CFS) self-drilling screw connections are popular in construction industry due to rapid fastening and ease of installation. However, the performance of the CFS connections is very critical when they are exposed to corrosive environments such as humid and acidic or chloride-rich environments. The corrosion damage of CFS structures when exposed to these environments can result in significant reduction of mechanical properties, which can affect the safety and durability of such structures. Very limited research is available in the literature to investigate the effect of corrosion on the behaviour of CFS connections. This issue is addressed herein through an experimental investigation. This paper presents a total of 36 new experiments on different types of CFS self-drilling screws (12 and 14 gauge) and steel sheet thickness (2.5 mm). Half of the tests were for corroded specimens and the remaining half were for non-corroded specimens. Further, one to two screws per arrangements connecting the steel sheets having yield strength of 450 MPa, were tested. Screws were immersed for 31 days and the CFS plates were immersed for 8 weeks in corrosion chamber before the tests were conducted. The experimental program was designed to investigate the effect of number of screws on shear strength of corroded specimens. Furthermore, a nonlinear explicit dynamic FE model was developed and validated against the experimental test results. The FE results were in reasonable agreement with the test results, both in terms of connection strength and failure modes.